2007
DOI: 10.1242/dev.02734
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafishatoh1genes: classic proneural activity in the inner ear and regulation by Fgf and Notch

Abstract: Hair cells of the inner ear develop from an equivalence group marked by expression of the proneural gene Atoh1. In mouse, Atoh1 is necessary for hair cell differentiation, but its role in specifying the equivalence group (proneural function) has been questioned and little is known about its upstream activators. We have addressed these issues in zebrafish. Two zebrafish homologs, atoh1a and atoh1b, are together necessary for hair cell development. These genes crossregulate each other but are differentially requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
279
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 177 publications
(298 citation statements)
references
References 60 publications
17
279
0
2
Order By: Relevance
“…In the zebrafish ear, the prosensory function is thought to be mediated by atoh1a/b genes (Millimaki et al, 2007). We showed that the posterior domain of atoh1a expression in the zebrafish inner ear appears later than the anterior domain, and is selectively affected by reducing Hh signaling.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…In the zebrafish ear, the prosensory function is thought to be mediated by atoh1a/b genes (Millimaki et al, 2007). We showed that the posterior domain of atoh1a expression in the zebrafish inner ear appears later than the anterior domain, and is selectively affected by reducing Hh signaling.…”
Section: Discussionmentioning
confidence: 77%
“…Tether cells and later-forming hair cells are specified in two distinct and successive phases. Their formation differentially requires the function of atoh1b and atoh1a respectively, two atonal homologs that have a proneural/prosensory function in zebrafish (Millimaki et al, 2007). Despite the common mechanisms leading to the formation of sensory cells in both maculae, anterior and posterior macula develops as two functionally specialized sensory epithelia.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fluorescent in situ hybridization (FISH) was performed at 55°C as published previously (Julich et al, 2005), followed by myosin-VI immunostaining and counterstaining with 4Ј,6Ј-diamidino-2-phenylindole (DAPI) (Invitrogen). Plasmids were cut and transcribed with the following for generating antisense digoxigenin-labeled RNA probes: Pme1/T7 for atoh1a (a gift from Bruce Riley, Texas A&M University, College Station, TX) (Millimaki et al, 2007); SalI/T7 for notch3 (clone NAA32G11; Open Biosystems, Huntsville, AL); XbaI/T7 for notch1a (a gift from Jose CamposOrtega; University of Cologne, Cologne, Germany) (Bierkamp and Campos-Ortega, 1993); SmaI/T3 for notch1b [cDNA in pBS-SK plasmid (Addgene, Cambridge, MA)] (Kortschak et al, 2001); EcoRI/T7 for deltaA and deltaD (a gift from Bruce Appel, Vanderbilt University, Nashville, TN) (Haddon et al, 1998b); ApaI/Sp6 for jagged1a; EcoRV/Sp6 for jagged1b; and SpeI/T7 for jagged2 (all jagged plasmids were gifts from Natasha Tiso, University of Padua, Padua, Italy) (Zecchin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%